Development of aqueous two‐phase systems comprising poly ethylene glycol and dextran for purification of pullulan: Phase diagrams and fiscal analysis. Issue 8 (24th May 2018) - Badhwar, Parul; Kumar, Punit; Dubey, Kashyap Kumar
Abstract: Pullulan is a commercially important Exopolysaccharide (EPS) with wide‐spread applications which is produced by Aureobasidium pullulans . The alternative α (1 4) & α (1 6) configuration in pullulan provides it the specific structural and conformational properties. Pullulan is currently being exploited in food, health care, pharmacy, lithography, cosmetics. The fermented broth is processed by organic solvent precipitation for isolation and purification of pullulan. In this study, we have tried to analyze the potential of aqueous two phase system as an alternate technique to extract pullulan from fermented broth. Including this viability of ATPS was also compared with conventional organic solvent precipitation system in terms of cost and time. It was found that ATPS process produced a higher yield of pullulan (80.56%) than organic solvent precipitation method (71.6%). ATPS was also found more economical and less time consuming method.